Status Motives, Hedonism, and Social Media Influencers as Drivers of Luxury Fashion Brand Preference among Generation Z: The Moderating Role of Cosmopolitanism in Serbia - Zdravković, Stefan (Anali Ekonomskog fakulteta u Subotici, 2026)
Purpose: The primary objective of this paper is to examine the effects of status motives, hedonism, and social media influencers on luxury fashion brand preferences among Generation Z consumers in Serbia. In addition, the study investigates the moderating role of cosmopolitanism in shaping these relationships. Methodology: The empirical research was conducted on a sample of 376 respondents belonging to Generation Z in Serbia. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and moderating effects. Findings: The findings indicate that status motives, hedonism, and social media influencers exert a significant positive influence on Generation Z consumers’ preferences for luxury fashion brands. Moreover, cosmopolitanism strengthens the impact of these determinants, suggesting that more cosmopolitan individuals are more responsive to symbolic, hedonic, and influencer-driven cues in luxury fashion consumption. Originality/value: This study contributes to the existing literature by integrating psychological motives, social media influence, and cosmopolitanism within a single empirical framework focused on Generation Z consumers. The research offers novel insights from an emerging market context, which remains underexplored in luxury fashion consumption studies. Practical implications: The results provide valuable guidance for luxury fashion brand managers and marketers by emphasizing the importance of status signaling, experiential value, and influencer marketing strategies tailored to cosmopolitan segments of Generation Z. The findings may also assist decision makers in designing more effective communication and branding strategies in digitally driven consumer markets. Limitations: The study is limited by its cross-sectional design and its focus on a single country, which may restrict the generalizability of the results to other cultural and market contexts. Additionally, the use of self-reported data may introduce potential response bias.